The impact of organizational values ​​on the quality of educational services from the point of view of faculty members: a field study on technical colleges in the city of Misrata (Economic studies journal, 2020)
This study aimed at investigating the low level of quality of educational services in the technical colleges in the City of Misurata as well as to identify the organizational values in the technical colleges from the point of view of teaching staff members. It also aimed to identify the quality of educational services provided by the technical colleges from the point of view of teaching staff members. The sample was selected in the random sample method, and the total number distributed was about (155), about (138) were valid for analysis. Statistical methods were used using the Spss program.The results of the study showed that the degree of impact of the organizational values was (medium) and the quality of the educational services was (weak). The study recommended that the management of the technical colleges in Misurata city should put attention to organizational values in the dimensions of (values of management of the organization, values of task management: values of management of relations, environmental management values) and their positive impact on the quality of educational services. In addition, the management of the technical colleges in Misurata city should take care of the quality of educational services in their institutions.
Keywords: Organisational values, Quality of educational services.